Risk factors for the progression of coronary artery calcification in asymptomatic subjects: results from the Multi-Ethnic Study of Atherosclerosis (MESA) - Kronmal, Richard A; McClelland, Robyn L; Detrano, Robert; Shea, Steven; Lima, João A; Cushman, Mary; Bild, Diane E; Burke, Gregory L (Circulation (New York, N.Y.), 2007)
The Multi-Ethnic Study of Atherosclerosis (MESA) provides an opportunity to study the association of traditional cardiovascular risk factors with the incidence and progression of coronary artery calcium (CAC) in a large community-based cohort with no evidence of clinical cardiovascular disease. Follow-up CAC measurements were available for 5756 participants with an average of 2.4 years between scans. The incidence of newly detectable CAC averaged 6.6% per year. Incidence increased steadily across age, ranging from <5% annually in those <50 years of age to >12% in those >80 years of age. Median annual change in CAC for those with existing calcification at baseline was 14 Agatston units for women and 21 Agatston units for men. Most traditional cardiovascular risk factors were associated with both the risk of developing new incident coronary calcium and increases in existing calcification. These included age, male gender, white race/ethnicity, hypertension, body mass index, diabetes mellitus, glucose, and family history of heart attack. Factors also existed that were related only to incident CAC risk, such as low- and high-density lipoprotein cholesterol and creatinine. Diabetes mellitus had the strongest association with CAC progression for blacks and the weakest for Hispanics, with intermediate associations for whites and Chinese. This is the first large multiethnic study reporting on the incidence and progression of CAC. Standard coronary risk factors were generally related to both CAC incidence and progression. Whites had more incident CAC and CAC progression than the other 3 racial/ethnic groups. Except for diabetes mellitus, risk factor relationships were similar across racial/ethnic groups.